New Diagnostic Applications in Sporotrichosis - Zancope-Oliveira, Rosely Maria; Almeida-Paes, Rodrigo de; Oliveira, Manoel Marques Evangelista de; Freitas, Dayvison Francis Saraiva; Galhardo, Maria Clara Gutierrez (IntechOpen, 2011)
None